Morphological and genetic differentiations revealed a new freshwater species of Gammarus from the French Pyrenees - Piscart, Christophe; Blanchet, Simon (Zootaxa, 2026)
This study describes morphologically and molecularly a new species, Gammarus ariegiensis sp. nov. from the Pyrenean Mountains in southern France. The new species is characterized by the lack of calceoli on the second antenna, the presence of long setae on anterior margin of merus and carpus of pereopod 5–7, endopodite of uropod 3 between 0.4 and 0.5 times the exopodite. A full description of the new species and information about its distribution is given in this paper together with molecular data (COI and 28S genes) corroborating the morphological delimitation of the new species.